Recent Rapid Rise of a Permethrin Knock Down Resistance Allele in Aedes aegypti in México - García, Gustavo Ponce; Flores, Adriana E.; Fernández-Salas, Ildefonso; Saavedra-Rodríguez, Karla; Reyes-Solis, Guadalupe; Lozano-Fuentes, Saul; Guillermo Bond, J.; Casas-Martínez, Mauricio; Ramsey, Janine M.; García-Rejón, Julián; Domínguez-Galera, Marco; Ranson, Hilary; et al. (PLOS Neglected Tropical Diseases, 2009)
Author Summary Pyrethroid insecticides prolong the opening of voltage-dependent sodium channels in insect nerves to produce instant paralysis and “knock-down.” Many insects have evolved knock-down resistance through nonsynonymous mutations that reduce pyrethroid binding in the channels. In 2006 we discovered one such mutation in the arbovirus mosquito vector Aedes aegypti, called Ile1,016, that confers very high knockdown resistance to the pyrethroid insecticide permethrin in mosquitoes homozygous for this mutation. We examined collections of Ae. aegypti from México during 1996–2009 and found that the overall Ile1,016 frequency increased from <0.1% in 1996–2000, to 2%–5% in 2003–2006, to 38.3%–88.3% in 2007–2009 depending upon collection location. We also demonstrate a strong linear relationship between the frequency of Ile1,016 homozygotes and knockdown rate in bioassays and speculate that widespread use of permethrin-based insecticides in México may be impacting the frequency of Ile1,016. Such a rapid increase is predicted by a simple model of positive directional selection acting on a recessive allele. Unfortunately this model also predicts rapid fixation of Ile1,016 unless there is a negative fitness associated with Ile1,016 in the absence of permethrin and if insecticidal pressure can be reduced.